THE APPLICATION OF QUANTUM LEARNING MODEL TO IMPROVE THE LEARNING OUTCOMES OF IPS CLASS STUDENTS VIII IN SMP NEGERI 1 MUARA RUPIT - Pitri Andika Sari, Agus Susilo, Isbandiyah, Pitri Andika Sari, (JURNAL EDUSCIENCE, 2024)
This study aims to determine the completion of social studies learning outcomes of class VIII students of SMP Negeri 1 Muara Rupit. The research method used is in the form of an experiment. The population is all class VIII students of SMP Negeri 1 Muara Rupit in the 2023/2024 academic year totaling 209 students and the research sample used is 1 class totaling 34 students. Data collection was carried out using the simple Random Sampling technique. The collected data were analyzed using a multiple-choice test totaling 30 questions. Based on the results of the data analysis, there was an increase in the average value in the Pre-test of 49.00 to 83.00 in the Post-test. The results of the post-test data analysis using the T test, the confidence level ɑ = 0.05 obtained tcount = 5.594 greater than ttable = 1.697, meaning that the hypothesis proposed in this study can be accepted as true because Ho is rejected and Ha is accepted for the results of social studies learning in class VIII students at SMP Negeri 1 Rupit.